GAMBARAN POLA ASUH IBU DENGAN STATUS GIZI BALITA USIA 6 – 59 BULAN DI DESA AJAOBAKI KECAMATAN MOLLO UTARA KABUPATEN TIMOR TENGAH SELATAN - maria pantaleon; Astuti Nur; Gestiviandi Lalian (Kupang Journal of Food and Nutrition Research, 2022)
At the basic stage, children`s needs are food (nutrition) this is the main element for children`s growth, so that children can grow according to their genetic abilities, in addition to needs in the physical aspect of children also need guidance, education and affection from parents so that children have the right to get good care because one of the factors that play an important role infulfilling children`s nutritional status is parenting (Soetjiningsih, 2015). The purpose of this study was to describe the practice of feeding children under five, health care parenting for toddlers, and sanitation parenting in families of toddlers with nutritional status of toddlers aged 6 – 59 months in Ajaobaki Village, North Mollo District, South Central Timor Regency. The sample in this study were parents of children aged 6 – 59 months totaling 32 people in Ajaobaki Village, North Mollo District, South Central Timor Regency. The search was conducted in Ajaobaki Village, North Mollo District, South Central Timor Regency. In February 2022. Based on the results of the study, it was shown that the parenting practice of feeding toddlers was in the good category, namely 18 people (56,2%). And the sufficient category was 14 people (43.8%). The health care parenting pattern for toddlers was in the good category, namely 19 people (59.4%), and the sufficient category 1 person (3.1%), sufficient category 10 people (31.2%), and poor category 21 people (65.6%).